Kebolehpasaran Graduan Wanita FKEE UTHM dalam Pemilihan Kerjaya - Endut, Safawati (Research and Innovation in Technical and Vocational Education and Training, 2025)
The field of engineering is often associated with men and makes women a minority in this field. Many higher education centers are opening up study opportunities in the field of engineering to women and making this group in line with the number of men with the progress of the new era. However, the level of marketability in this field for women is often disputed due to many factors. This study aims to examine the level of marketability of female graduates at UTHM’s Faculty of Electrical and Electronics Engineering in career selection because there are almost 50% of female graduates who do not work in their respective fields of study. The design of this study is in the form of a survey using a quantitative approach and questionnaires are distributed online to obtain research data. A total of 196 female graduates responded to the questionnaire. The data of the study was analyzed using the Statistical Package for Social Sciences (SPSS) version 27.0 such as descriptive analysis, mean score, standard deviation, inference analysis, percentage, regression test and T-test. The findings of this study show that family support and workplace location play a large role in job selection decisions for female graduates. This is followed by a moderate influence effect which is academic achievement while salary expectation not in line with the job is the weakest factor in their career choice.